The Impact of Gender Diversity and Capital Adequacy on ESG Disclosure, Mediated by Financial Performance in KBMI 3 & 4 Banks - Azka Amany; Indra Siswanti (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
This research aims to analyze the influence of green finance, gender diversity, and capital adequacy on Environmental, Social, and Governance (ESG) disclosure, with financial performance (ROA) as a mediating variable, focusing on banks in the KBMI 3 and 4 categories for the 2021-2024 period. The background of this study is driven by the increasing demand for sustainability transparency in the banking sector and the importance of understanding the mechanisms that encourage comprehensive ESG disclosure. The research methodology employs a quantitative approach using panel data from 10 KBMI 3 and 4 category banks listed on the Indonesia Stock Exchange between 2021 and 2024, utilizing path analysis and the Sobel test. Data were sourced from annual reports and Refinitiv Eikon ESG scores. The results indicate that green finance, gender diversity, and capital adequacy do not have a significant direct effect on ESG disclosure. Conversely, financial performance (ROA) is proven to have a significant positive effect on ESG disclosure and is able to partially mediate the influence of green finance and capital adequacy; however, it does not mediate the effect of gender diversity on ESG disclosure. These findings underscore the importance of improving financial performance to drive sustainability practices in the banking sector, as well as the need for policies that encourage more effective integration between financial and non-financial aspects in sustainability reporting.